Food Security: At what cost? Dietary and behavioural coping strategies of low-income households in Cairo and implications on children’s food security - Saad, Radwa (AUC Knowledge Fountain, 2014)
This study explores the dietary and behavioural coping strategies employed by low-income households in urban poverty pockets of Greater Cairo in response to food price fluctuations. It investigates the impact of nutrition-related coping behaviours on the food security of households, focusing namely on children and youth. The study uses qualitative research in the form of in-depth interviews, focus group discussions and key informant interviews with mothers residing in one of the largest informal settlements of Cairo, to arrive at an in-depth analysis of the problem. The research reveals that low-income households employ poor coping strategies in response to high food prices that could potentially further their food insecurity and perpetuate the cycle of poverty within which they live. As will be discussed in this paper, replacing nutritious foods with cheaper alternatives, eliminating meals, rationing household consumption, and resorting to dangerous eating behaviours are among many of the detrimental coping strategies households were found to employ. The study concludes with policy recommendations and future courses of action to combat the progression of food insecurity among vulnerable households and prevent the further decline of nutritional statuses in response to increasing food prices.